Pengaruh Kualitas Kepuasan dan Pelayanan terhadap Loyalitas Pengguna Kawasan Industri - Lesmana, Hendra (Universitas Brawijaya, Indonesia, 2016)
This study aimed to examine the influence of satisfaction and service the industrial estates to the loyalty of the user of industrial estates. The methods using Structural Equation Model (SEM). Primary data obtained directly from the respondents by filling the questionnaire, the method of filling the questionnaire conducted by direct interview with the respondents. Primary data contains the company's perception the users of industrial estatesto various services provided by the company's industrial estates. Research findings indicate the Government is very concerned about growth and development of industrial estates throughout the country. These interests can be viewed directly or indirectly. Direct interest shown in State revenue, more and more industrial estates grow and develop, then the more taxes to be gained. While the indirect presence of an industrial estates can open wide enough jobs for all the people and driven economic growth more broadly. Based on the findings of which have been disclosed previously, user loyalty of industrial estates is not only determined by the quality of services provided by the company but also the industrial estates influenced by external factors, including government support. Therefore, the government is expected to provide support for the growth and development of industrial estates through the issuance of legal rules which protect the entrepreneurs and companies in a fair and transparent.Â